Perkembangan Bahasa Anak Kelompok B Kelas Umar Di TK An Nizam - Juliana Br.Pandiangan; Preity Debora Br.Sembiring; Trina Dara Br.Sinuraya; Eva Eva (Universitas Palangka Raya, 2024)
Children's language development is carried out in a systematic way and develops according to the child's increasing age. This research aims to find out how the language development of children aged 6 years. The research was conducted at AN NIZAM Kindergarten with the research subjects being children in Umar's class. This research was carried out using observation and guided interview methods. Observations on the language development of children aged 6 years were carried out using a questionnaire that had been developed. Quantitative data that has been collected through guided observation is analyzed using descriptive statistics, while qualitative data from interviews is analyzed using qualitative data analysis methods. The results of the research show that aspects of the language development of 6 year old children in Umar's class at An Nizam Kindergarten can be categorized as well developed.